Utility of vest high frequency chest wall oscillation device versus flutter device in acute exacerbation of chronic obstructive pulmonary disease - S. Farag, Taghreed; EL-Syed, Mariam (International Journal of Research in Medical Sciences, 2017)
Background: Objectives to assess the effectiveness of high frequency chest wall oscillation (HFCWO) vest system and Flutter devices in the treatment of patients with AECOPD, and to compare the efficacy of HFCWO vest system versus Flutter devices. Methods: We conducted an interventional study on 108 out of 129 patients presented with AECOPD, recruited from two-university hospitals. They were classified into three groups, HFCWO group (n=37), Flutter group (n=35), and control group (n=36). The HFCWO group and Flutter group were treated with AECOPD medications in addition to either HFCWO or Flutter physiotherapy, three sessions per week, for four weeks, while control group was treated by medications only. All patients were evaluated before and after treatment by spirometry, ABG, CAT score, and the BODE index. Results: Post treatment assessment for both HFCWO and Flutter groups demonstrated that most of spirometric indices (FEV1%, FVC%, FEV1/FVC %), oxygenations parameters (PaO2, SaO2 %) and CAT score, were significantly improved (p < 0.05). The level of perceived dyspnea decreased significantly, walking distance during 6-MWT was extended significantly, the BODE index and MMRC scale decreased significantly. While in control group only oxygenations parameters (PaO2, SaO2 %) was mildly improved. No statistical significant difference was found between vest HFCWO and Flutter device in all measured post treatment parameters (p > 0.05). Conclusions: Both vest HFCWO and Flutter device are highly effective in treatment of patients with AECOPD in terms of improvement in ventilatory function and oxygenation parameters with better exercise tolerance.